The question of location of public housing developments at CDHU on the urban space - Namur, Marly (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
This paper discusses the role of the State in the process of public production of urban space, as the developer of social interest housing projects, as well as the possible speculative profits for land-owners that results from the choice of project location. It is emphasized that the location of the housing projects is an inductor of urban development and has direct implications on urban quality of life for the dwellers, due to the distances that are defined in relation to urban services and commerce.. The definition and implementation of the land acquisition and provision policy of the Urban and Housing Development Company of the State of São Paulo (CDHU) is discussed, including the progressive reduction of implementation costs and service and infrastructure costs, and the interruption of the growth of urban land in the city outskirts, as an attempt to avoid social exclusion of dwellers. Finally, the application of the Statute of the City is pointed out. This legal instrument has increased the possibilities for the local government to purchase land in urban areas, in order to reduce speculative profits.